Case report: Microsurgical resection of a giant triple dumbbell shaped jugular foramen Schwannoma via retrosigmoid and transcervical approach - Sun, Haiying; Hu, Yujuan; Zhu, Yun; Hu, Juanjuan; Yuan, Jie; He, Zuhong; Cheng, Huamao (Frontiers in Oncology, 2024)
The surgical management of extensive jugular foramen schwannomas presents a formidable challenge, aiming for gross total resection while minimizing complications. Here, we present a case with giant triple dumbbell-shaped jugular Foramen Schwannoma. A 45-year-old male with a one-year history of a left neck mass underwent surgery. Initial misdiagnosis of submandibular gland inflammation led to persistent symptoms despite anti-inflammatory treatment. Imaging revealed a large lesion in the left cerebellar peduncle-neck-jugular foramen region (39.6 x 26.2 x 90 mm). The combination of retrosigmoid and transcervical approach was selected. Sufficient drilling of the infralabyrinthine, retrofacial area of the mastoid with facial nerve transposition is important for the safe gross total removal of the tumor. The patient underwent a gross total removal of the tumor. Facial nerve function was preserved. Although dysphagia and hoarseness complicated postoperatively, he became able to take foods orally after the surgery. In conclusion, this case underscores the successful surgical approach for a large jugular foramen Schwannoma, emphasizing the importance of precise techniques to achieve complete tumor resection while minimizing postoperative complications.